Identification of potential ferroptosis-associated biomarkers in rheumatoid arthritis - He, Xu; Zhang, Juqi; Gong, Mingli; Gu, Yanlun; Dong, Bingqi; Pang, Xiaocong; Zhang, Chenglong; Cui, Yimin (Frontiers in Immunology, 2023)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by inflammation and gradual joint degeneration. Recently, ferroptosis, a novel form of regulated cell death that involves iron-dependent lipid peroxidation, has been implicated in RA pathogenesis . However, the underlying mechanisms and key genes involved in ferroptosis in RA remain largely unknown. Methods: The GSE134420 and GSE77298 datasets were downloaded and DEGs were identified using R software. The DEGs were then mapped to the dataset of 619 ferroptosis-related genes obtained from the GeneCards database. GO and KEGG analyses were conducted to investigate the possible biological functions. PPI networks were constructed to identify the hub genes. The relationship between hub genes and immune infiltration was estimated using CIBERSORT. GSEA was used to explore the underlying signaling pathways of hub genes. GWAS analysis was performed to confirm the pathogenic regions of the hub genes. RcisTarget and Gene-motif ranking databases were used to identify TFs associated with the hub genes. The miRcode databases were utilized to construct the miRNA-mRNA network. Single-cell analysis was utilized to cluster cells and display the expression of hub genes in cell clusters. Finally, the expression and potential mechanism of hub genes were investigated in human and experimental samples. Results: Three hub genes PTGS2, ENO1, and GRN highly associated with ferroptosis were identified. Four pathogenic genes HLA-B, MIF, PSTPIP, TLR1 were identified that correlated significantly and positively with the expression levels of hub genes. The results of the GSEA showed that the hub genes were significantly enriched in pathways related to immunity, lysosome, phagocytosis and infection. ENO1 and PTGS2 were enriched in the TF-binding motif of cisbp_M5493. The hub genes were validated in experimental and patient samples and highly level of ENO1 expression was found to inhibit ACO1, which reduces ferroptosis in proliferating FLS. Conclusions： PTGS2, ENO1 and GRN were identified and validated as potential ferroptosis-related biomarkers. Our work first revealed that ENO1 is highly expressed in RA synovium and that ferroptosis may be regulated by the ENO1-ACO1 axis, advancing the understanding of the underlying ferroptosis-related mechanisms of synovial proliferation and providing potential diagnostic and therapeutic targets for RA.